Factors Affecting Satisfaction on Online Education on Students Digital Teaching Page in Ho Chi Minh City, Vietnam - Anh, Doan Huynh Mai (Indonesian Journal of Multidiciplinary Research, 2022)
Student satisfaction is of utmost importance to universities. Understanding that problem, factors affecting the satisfaction of online education on the digital teaching page of students in Ho Chi Minh City were studied to give suggestions to universities to improve the satisfaction of online education. satisfaction as well as the quality of online teaching. From the theoretical basis and research model of the available studies, we have adjusted and come up with our formal research model. The research methods are qualitative and quantitative methods. The questionnaire was processed by SPSS with techniques to evaluate the reliability of the scale through Cronbach Alpha coefficient, EFA factor analysis to identify groups of variables to include in multiple regression analysis. The results showed that there are two groups of variables affecting student satisfaction arranged in descending order: Lecturer and Interaction, Course overview. An overview of studies in the world shows research on factors affecting online learning. Studies in the world conducted from 1989 to the present have changed a lot in terms of research contents and methods with many different angles in many countries. Meanwhile, in Vietnam, studies on this issue have only been carried out in recent years, mainly in the direction of assessing the impact of factors on learning outcomes without any comprehensive research. assess the factors affecting student satisfaction, propose measures suitable to the current context to overcome, and have a better overview of the problem. Therefore, this study was conducted to fill in this research gap.